2019
DOI: 10.1101/543264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome wide analysis ofGa1-smodifiers in maize

Abstract: A one way reproductive barrier exists between most popcorn varieties and dent corn varieties grown in the United States. This barrier is predominantly controlled by the ga1 locus. Using data from a diverse population of popcorn accessions pollinated by a dent corn tester, we found that the non-reciprocal pollination barrier conferred by ga1 is more complex than previously described. Individual accessions ranged from 0% to 100% compatible with dent corn pollen. Using conventional genotyping-by-sequencing data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Because all hybrids contained the same allele of Ga1-s, these differences cannot be due to effects of the Ga1-s allele. In light of previous studies that have identified modifier loci in homozygous lines (Hurst et al, 2019;Shrestha, 2016), the most likely explanation for these differences is modifier loci present within the genetic backgrounds included in this study. We cannot rule out that allelic effects due to the ga1 allele carried by each hybrid exist, since the different hybrids probably have different structural variants of their ga1 alleles; however, the ga1/ga1 parent lines have been observed extensively and pollen exclusion has not been reported.…”
Section: Discussionmentioning
confidence: 80%
“…Because all hybrids contained the same allele of Ga1-s, these differences cannot be due to effects of the Ga1-s allele. In light of previous studies that have identified modifier loci in homozygous lines (Hurst et al, 2019;Shrestha, 2016), the most likely explanation for these differences is modifier loci present within the genetic backgrounds included in this study. We cannot rule out that allelic effects due to the ga1 allele carried by each hybrid exist, since the different hybrids probably have different structural variants of their ga1 alleles; however, the ga1/ga1 parent lines have been observed extensively and pollen exclusion has not been reported.…”
Section: Discussionmentioning
confidence: 80%
“…A similar study searching for the modifiers of the gametophyte factor Ga1s showed evidence of significant QTL on chromosomes 4 and 10 (Shrestha 2016). Similarly, a genome-wide association study by Hurst ( 2019) identified seven significant SNPs as possible modifiers of the Ga1-s system (Hurst et al 2019). It is currently unknown whether these modifiers and their molecular mechanisms are unique or shared between cross-incompatibility systems.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which Ga1-s corn lines can exclude unwanted pollen is complicated by genetic background and zygosity of the Ga1-s locus 9 . In addition, QTL for genetic modifiers have been shown to effect pollen exclusion in popcorn 12 . Researchers examined representatives from Supergold, Amber Pearl, and South American popcorn heterotic groups for the presence of genetic loci that alter the ability of Ga1-s to exclude ga1/ga1 pollen.…”
Section: Introductionmentioning
confidence: 99%